Effectiveness of song-and-movement creative arts on children’s motor skills during the transition to Primary School - Palupi, Warananingtyas; Novitasari, Danella Ayu; K.P., Alyana Suciparasati; Rahmawati, Anayanti; Pudyaningtyas, Adriani Rahma; Kusumadewi, Nurul; Sholeha, Vera; Ricardos, Glenn Webforges D. (Universitas Ahmad Dahlan, 2026)
Purpose – Gross motor readiness is an important but often undervalued aspect of children’s transition from early childhood education to primary school. Although song-and-movement activities are widely used in Indonesian PAUD settings, their effects on children’s gross motor readiness are still rarely tested through structured intervention and standardized indicators. This study therefore examined the effectiveness of a structured song-and-movement intervention on gross motor development among preschool children during the transition to primary school. Design/methods/approach – A pre-experimental one-group pre-test and post-test design was used with 16 children aged 5–6 years in a PAUD institution in Karanganyar, Indonesia. The intervention was conducted over 8 weeks in 16 sessions using the “Aramsamsam” song-and-movement activity. Gross motor skills were assessed through five indicators: balance, strength, agility, coordination, and flexibility. Data were analysed using Shapiro-Wilk and paired-samples t-test. Findings – Children’s mean gross motor score increased from 8.81 (SD = 2.316) at pretest to 14.75 (SD = 3.088) at post-test. The difference was statistically significant (t = -20.102, df = 15, p < .001), with a very large effect size (Cohen’s d = 5.026; Hedges’ g = 4.899). The largest gains were found in coordination (1.43) and balance (1.37). Research implications/limitations – The findings suggest that structured rhythm-based movement activities may enhance motor readiness during school transition. However, the absence of a control group limits causal interpretation. Further randomized studies are recommended. Practical implications – Structured rhythm-based movement activities can be incorporated into early childhood classrooms as a playful strategy to support children’s motor readiness for school transition. Originality/value – This study contributes empirical evidence from Indonesia on the role of rhythm-structured song-and-movement activities in enhancing specific gross motor domains during the transition to primary school.